Comparison of calibration of surface contamination monitors with Brazilian Network – 2018/2019. Issue 1 (March 2021) - Cabral, TS; Laranjeira, A S; Potiens, MPA; Soares, CMA; Khoury, H; Saito, V; David, M.; Vidal, L.C.; Pires, MA
Abstract: This work reports the results obtained from the comparison involving 7 laboratories in Brazil. This exercise is about the calibration service of surface contamination monitors. The monitor has been calibrated to BS ISO 7503-3, the calibration factor in terms of surface emission rate. The comparison was conducted by the Brazilian National Laboratory of Ionizing Radiation Metrology (LNMRI / IRD) from October 2018 to July 2019. The extensive sources used were 14 C, 137 Cs, 60 Co, 90 Sr/ 90 Y, 36 Cl and 241 Am. The result of this proficiency test was excellent and proved the calibration capacity of the Brazilian network in the calibration service for surface contamination monitors.